The bright side of the internal labor market: Evidence from the labor cost stickiness of firms affiliated with privately owned business groups in China - Xu, Hui; Chan, Kam C.; Na, Chaohong; Fang, Qiaoling (Journal of Corporate Finance, 2023)
We examine whether having an internal labor market can help a firm affiliated with a privately owned business group (POBG) reduce labor cost stickiness. Our findings suggest that, when a POBG-affiliated firm experiences a decrease in sales, it has lower labor cost stickiness than an otherwise equivalent firm that is not affiliated with a POBG. Specifically, we find that, on average, a POBG-affiliated firm entirely mitigates labor cost stickiness when it has a decrease in sales. In addition, we document that, to adjust its labor cost downward, a POBG-affiliated firm hires fewer employees, rather than paying lower wages. We show that the lower labor cost stickiness is due to movement of employees from the focal firm to other firms within the same POBG. When sales fall, the POBG reallocates excess employees at the focal firm to other firms within the business group via an internal labor market, and the focal firm thereby increases its per capita profit. Moreover, we find that agency cost mediates the impact of a POBG on labor cost stickiness. When the external market is less effective or the POBG headquarters have strong incentives, the effect of POBG affiliation on the reduction in an affiliated firm's labor cost stickiness is more salient.